LKPD Development On MEAs Based-Approach to Improve the Mathematical Representation Ability of Grade X Students - Riren Rostari; Irwan Irwan; Yulkifli Yulkifli (International Journal of Research in Counseling and Education, 2017)
LKPD used in school had not been optimal in helping students to improve the mathematical representation ability. It happened because the used LKPD was giving a less opportunity to the students to solve the mathematical representation problems. One of the solutions to do about that problem is to develop LKPD-Modeling Eliciting Activities (MEAs) based approach. The purpose of this study is to produce a valid, practical and effective LKPD-MEAs based approach to improve the students’ mathematical representation. This study is a development research using Plomp model which consists of Preliminary Research, Development or Prototyping and Assessment Phase. The subjects of this study were X grade students of SMAN 3 Padang. The instruments used were LKPD validation sheets, teacher’s response questionnaires, students’ response questionnaires and test. The result of this study is a valid, practical and effective LKPD-MEAs based approach with an average of each is 0,728,  85,39 and 82,41.